A Study on Passengers’ Perception of Service Quality Offered At Ibrahim Nasir International Airport, Republic Of Maldives - Mohamed, Naseeh (2012)
This research is an analysis of the perception of passengers using Ibrahim Nasir International Airport (INIA), Republic of Maldives, on the quality of service offered to them at the airport. Using the SERVQUAL model and data gathered via an online survey of passengers who had used the international passenger terminal of NIA during the past three months, a thorough analysis was conducted on the factors which affect the passengers’ perception of airport service quality and areas which needed to be improved were identified. Also, the relationship between the passengers’ perception of service quality and passenger satisfaction, and the gap between the perceived service quality and expected service quality were also analysed. Finally, a conceptual model for measuring perceived airport service quality was formulated based on the information gathered.